Gamification Using Visual Novel to Improve Chemistry Learning Motivation - Louis Khrisna Putera Suryapranata; Felix Intan Bahagia; Irene Astuti Lazarusli (Journal of Games, Game Art, and Gamification, 2023)
Learning chemistry at the beginning of senior high school is difficult because there is too much information that should be remembered, especially the periodic table. To reduce the difficulty of students’ learning processes, gamification could be helpful. In this study, gamification applications in the form of a visual novel have been developed and focused on the periodic table material for 1st-year senior high school students. The motivation improvement had been measured using the IMMS (Instructional Materials Motivation Survey) questionnaire in the pre-test and post-test sections. Respondents filled out the pre-test at the beginning of the experiment, followed by a visual novel playing session for one week. After the playing session ended, the respondent filled out the post-test. The motivation score from the pre-test and the post-test result had been compared using a paired T-test to see whether there was an improvement in learning motivation. It could be concluded that improvement in learning motivation happened due to the usage of visual novels, with an overall motivation score improvement of around 18.61%. In the future, this study will be continued by applying user personalization according to learning style preferences.